Strategi Penerapan Konsep Green Economy dan Budaya Cashless Pada Objek Wisata Grand Maerakaca Kota Semarang - Sari, Anggita Novita; Agustina, Refi; Siagian, Puri Ayu Agustina (Fakultas Syariah dan Ekonomi Islam Institut Pesantren Mathali'ul Falah, 2022)
Bank Indonesia (BI) launched the National Non-Cash Movement (GNNT) on August 14, 2014 which aims to create a safe, efficient and smooth payment system, which in turn will be able to encourage the national financial system to work effectively and efficiently so as to create an ecosystem. cashless society. Cashless transactions are a form of payment system transformation that has touched various aspects of life, one of which is tourism. The city of Semarang is known as the cleanest tourist destination and is a city that has started implementing a cashless culture in several tourist attractions. However, there are several tourist attractions that still have not implemented the system due to lack of education about the importance of adapting to the times. As experienced by the Grand Maerakaca tourist attraction, which is a business unit owned by PT. PRPP Central Java. The non-enforcement of cashless culture is a problem for Grand Maerakaca tourism objects, especially regarding transparency. Another problem is the prohibition of MSME actors from selling at the Grand Maerakaca tourist attraction for reasons of cleanliness. This study uses a descriptive qualitative approach using primary data (interviews, observations) and secondary data (libraries, documentaries).